Metrological assurance features of virtual measuring instruments - Павлов, Євген Олександрович (Technology audit and production reserves, 2014)
The features of modern virtual measuring instruments, which are widely used nowadays, are described in the paper. The analysis of problems of using virtual measuring instruments, which have terminological and metrological aspects is presented. The absence of standardized terms and concepts in the field of virtual measurements in both the national and the international normative documents was established. The state of metrological assurance of virtual measuring instruments, which covers the issues of metrological software certification, metrological self-checking, establishing and rationing of metrological features of virtual instruments, their verification and calibration features, was analyzed. It was found that nowadays virtual measurements are not fully supported by normative-methodological base. The necessity of taking into account the metrological assurance features of virtual measuring instruments in the existing normative documents and their harmonization with international normative documents was shown.